2022
DOI: 10.1007/s40195-022-01461-z
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-Induced Strengthening Mechanism in a Newly Designed L-40 Tool Steel Manufactured by Laser Powder Bed Fusion

Abstract: The microstructural and mechanical properties of a newly designed tool steel (L-40), specifically designed to be employed in the laser powder bed fusion (LPBF) technique, were examined. Melt pool boundaries with submicron dendritic structures and about 14% retained austenite phase were evident after printing. The grain orientation after high cooling rate solidification is mostly < 110 > α ∥ building direction (BD). Then, the heat treatment converted the microstructure into a conventional martensitic phase, red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…Of the three manufacturing steps (casting, forging, and heat treatment), forging is where the most-important microstructural changes take place, which greatly influence the final properties that can be achieved [4][5][6]. The open die forging process is fundamentally a hot compression process during which work strengthening effects, such as hardening (WH) and precipitation, take place concomitantly with softening phenomena such as recovery and recrystallization under static and/or dynamic thermomechanical loads [7,8]. It has also been reported that phase transformation can occur during deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Of the three manufacturing steps (casting, forging, and heat treatment), forging is where the most-important microstructural changes take place, which greatly influence the final properties that can be achieved [4][5][6]. The open die forging process is fundamentally a hot compression process during which work strengthening effects, such as hardening (WH) and precipitation, take place concomitantly with softening phenomena such as recovery and recrystallization under static and/or dynamic thermomechanical loads [7,8]. It has also been reported that phase transformation can occur during deformation.…”
Section: Introductionmentioning
confidence: 99%